Both encouraging feeding style and high energy density may increase energy intakes from fermented millet gruels eaten by infants and toddlers in Ouagadougou. (1st April 2016) - Mouquet-Rivier, Claire; Traoré, Tahirou; Soma, Adama; Kaboré, Claire; Trèche, Serge
Abstract: Traditional fermented millet gruel is frequently eaten by children in Burkina Faso as a complementary food or for breakfast. The effects of gruel energy density and feeding style on intakes (amounts and energy) were assessed in children in Ouagadougou. Twenty-three young children (11 infants and 12 toddlers) were given two meals of gruel per day for two periods of 11 consecutive days, first, the traditional fermented gruel (TFG), and second, an improved high energy density fermented gruel (IFG). On the first 10 days of each period, the children were fed as usual, while on the 11th day, the mothers were asked to use encouraging feeding. Intakes of TFG and IFG were also measured once a day for nine days in 25 preschoolers (2-5 years-old). After adjustment for the subject effect, IFG intakes did not significantly differ from TFG intakes in the groups of infants and toddlers, meaning there was a significant increase in energy intakes, which almost doubled. Encouraging feeding increased TFG intakes in both age groups, but IFG intakes only increased in toddlers, whose energy intake tripled compared to that from TFG with the usual feeding style. In preschoolers, mean IFG intakes were lower than TFG intakes and there were no increase in mean energy intakes. Improving fermented gruel and training the mothers to encourage their young children during feeding are two possible strategies to improve food intakes, and hence to better satisfy the children's nutritional needs. Highlights: Improved fermented millet gruel increased energy intakes in infants and toddlers. In preschool children, the improved gruel did not increase energy intakes. Encouraging feeding significantly increased infants and toddlers' gruel intakes. Benefits of encouraging feeding and improved gruel were cumulative in toddlers.